Implementing an Antibiotic Stewardship Program: Guidelines by the Infectious Diseases Society of America and the Society for Healthcare Epidemiology of America. (13th April 2016) - Barlam, Tamar F.; Cosgrove, Sara E.; Abbo, Lilian M.; MacDougall, Conan; Schuetz, Audrey N.; Septimus, Edward J.; Srinivasan, Arjun; Dellit, Timothy H.; Falck-Ytter, Yngve T.; Fishman, Neil O.; Hamilton, Cindy W.; Jenkins, Timothy C.; et al.
Abstract: Evidence-based guidelines for implementation and measurement of antibiotic stewardship interventions in inpatient populations including long-term care were prepared by a multidisciplinary expert panel of the Infectious Diseases Society of America and the Society for Healthcare Epidemiology of America. The panel included clinicians and investigators representing internal medicine, emergency medicine, microbiology, critical care, surgery, epidemiology, pharmacy, and adult and pediatric infectious diseases specialties. These recommendations address the best approaches for antibiotic stewardship programs to influence the optimal use of antibiotics.